Jack hang door / Noraniezah Narol … [et al.] - Narol, Noraniezah; Nik Zakaria, Nik Izni; Ismail, Nora; Salleh, Syahidah; Abd. Umar, Zaidah (Division of Research, Industrial Linkages and Alumni, UiTM Cawangan Melaka, 2013)
Door installation work will be done after the super structure and after the finishing work on the building. This requires the construction process as soon as possible. It usually required more than a worker to carry it. Generally, we can see the procedure or skills applied in door installation. Works of door assembly need a lot of strength and energy to make sure the door fixed to the door frame and follows the requirement of specifications. There are several problems arise during the door installation works carried out such as the employer have to face high labor costs, injuries to employees and health implications such as backache and others. In addition, door installation works often take a long time because workers had to be careful when lifting the door to the frame, then the hinge can be installed. This product research would help to simplify work and most importantly help to reduce time and costs involved. It also shows the specific usage of Jack Hang Door which provided against difficulties and suitable for varies types of door or in furniture manufacture works. Based on Fixed Pulley System concept which the combination of non-corrosion metal (hollow metal) and bolt and nut which produce a foot-operated product which based on its foundation stability. Hence, it is perhaps that it will be inspirational to produce Jack Hang Door product thus acknowledging as a practical and economic inventory.